Stent Placement in the Hepatic Artery with Anatomical Variant for Treatment of A Massive Ulcer Bleeding - B, Van Dijk; WH, de Vos tot Nederveen Cappel; BAAM, van Hasselt; HL, van Westreenen; VB, Nieuwenhuijs (Archives of Clinical and Medical Case Reports, 2021)
A 54-year-old man, presented with melaena after a recent bowel perforation resulting in sigmoid resection. The gastroduodenoscopy showed a large clot and active bleeding in the postpyloric duodenum without the opportunity of obtaining endoscopic hemostasis. A diagnostic angiography was attempted, but no blush was seen. The next day radiologic coiling took place. Unfortunately long term hemostasis was not achieved. A second gastroscopy was performed and a postpyloric ulcer with a large pulsating blood vessel was seen. Hemostasis was attempted by both endoscopic clipping and radiological coiling of the target vessels. An angiography with coiling was attempted. It was technically impossible to coil all the vessels due to an anatomic variation. In order to prevent to sacrify the hepatic artery by coiling the entire hepatic artery, we successfully tried a unique approach to place a radiologic covered stent in the common hepatic artery to cover the origin of the gastroduodenal artery.